Developing Reading Materials Based on the Student’s Multiple Intelligence Types for Junior High School Students - Setyowati, Hanie Ika; Sugirin, Sugirin (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
Abstract: Students are unique with their characteristics and differences. In line with the current learning paradigm, learner-centered paradigm, teaching and learning process places greater emphasis on individuality. One of the differences is multiple intelligence types possessed by all individuals resulting in various ways of learning. Learning materials, one of the learning resources, ideally have to accommodate the students’ multiple intelligence types. However, the current learning materials contain neither sufficient reading texts nor tasks fostering their multiple intelligence types that happen in every classroom. Thus, this research intends to develop reading materials based on multiple intelligence to accommodate students’ intelligence. This research belongs to research and development of which steps are conducting a needs analysis, developing the product, getting an expert judgement, trying-out the materials and revising the product (Gall, Gall Borg, 2007). In order to develop the appropriate reading materials that meet the students’ needs, a needs analysis was initially conducted. The needs analysis was conducted in five junior high schools in Magelang district including state and private schools. The data of the needs analysis were obtained by distributing questionnaires which were used as the consideration in developing the materials. Then, the materials developed were validated by material and learning experts before being tried out at SMP N 1 Windusari, Magelang to complete and to perfect the materials. From the data analysis, the average score of the appropriateness of the content, the language, the presentation and the design of the materials was 3.54 which was classified as “very good” and “appropriate” to be implemented. Furthermore, the result indicated that the materials also fulfilled the criteria of good materials, for instance, considering that students are different. Thus, teachers and educational stakeholders should develop learning materials catering to the students’ multiple intelligence types to accommodate their differences.Key words: reading materials, differences, multiple intelligence